Financial Accounting / Seventh Edition - Needles Belverd E; Powers Marian Ph. D (Houghton Mifflin Company, 2001)
Preface, Accounting as an Information System, Uses of Accounting Information and the Financial Statements, Measuring Business Transactions, Measuring Business Income, Accounting Systems, Financial Reporting and Analysis, Measuring and Reporting the Operating Cycle, Merchandising Operations and Internal Control, Short-Term Liquid Assets, Inventories, Current Liabilities and the Time Value of Money, Measuring and Reporting Long-Term Assets and Long-Term Reporting, Long-Term Assets, Long-Term Liabilities, Contributed Capital, Expanded Presentation and Analysis of Accounting Information, The Corporate Income Statement and the Statement of Stockholders' Equity, The Statement of Cash Flows, Financial Statement Analysis, International Accounting and Long-Term Investments, Appendices, The Merchandising Work Sheet and Closing Entries, Special-Purpose Journals, Accounting for Unicorporated Businesses, Future Value and Present Value Tables, Company Names and Subject Index.
Preface, Accounting as an Information System, Uses of Accounting Information and the Financial Statements, Measuring Business Transactions, Measuring Business Income, Accounting Systems, Financial Reporting and Analysis, Measuring and Reporting the Operating Cycle, Merchandising Operations and Internal Control, Short-Term Liquid Assets, Inventories, Current Liabilities and the Time Value of Money, Measuring and Reporting Long-Term Assets and Long-Term Reporting, Long-Term Assets, Long-Term Liabilities, Contributed Capital, Expanded Presentation and Analysis of Accounting Information, The Corporate Income Statement and the Statement of Stockholders' Equity, The Statement of Cash Flows, Financial Statement Analysis, International Accounting and Long-Term Investments, Appendices, The Merchandising Work Sheet and Closing Entries, Special-Purpose Journals, Accounting for Unicorporated Businesses, Future Value and Present Value Tables, Company Names and Subject Index.